Developing labour market analysis and forecasting methods in Malta - Sundqvist, Jan; Camilleri, Edwin (Stockholm, 2004)
"The third report is a report from a forecasting project in Malta. It is written by Jan Sundqvist who was stationed in Malta and worked on the project from February until May 2002 and Edwin Camilleri from the Employment and Training Corporation, ETC, in Malta."